Formulasi Tablet Hisap Ekstrak Etanol Umbi Sarang Semut Asal Kalimantan Tengah - Sartika, Fera; Handayanai , Rezqi; Rahmawati , Ade Catur (Universitas Borneo Lestari, 2026)
Central Kalimantan is one of the provinces in Indonesia that annually experiences haze disasters caused by forest and land fires, leading to significant negative health impacts, such as the prevalence of Acute Respiratory Infections (ARI). One of the local community's efforts to manage ARI involves utilizing medicinal plants as traditional therapy, specifically the Sarang Semut tuber (Myrmecodia tuberosa Jack). According to previous studies, the ethanolic extract of Sarang Semut tuber contains secondary metabolites, including alkaloids, flavonoids, saponins, quinones, tannins, steroids, and triterpenoids. The objective of this research is to develop an innovative pharmaceutical formulation in the form of lozenges using the ethanolic extract of Sarang Semut tuber as the active ingredient. The lozenges were prepared using the wet granulation method, with a target tablet weight of 500 mg. The formulation varied the ratio of fillers, specifically mannitol-sucrose, across three formulas: F I (75:25), F II (50:50), dan F III (25:75). The tablets were evaluated through physical property tests, including organoleptic properties, weight and size uniformity, hardness, friability, and disintegration time. The results demonstrated that the ethanolic extract of Sarang Semut tuber can be successfully formulated into lozenges with physical characteristics that meet evaluation standards, particularly Formula III. The resulting lozenges exhibited an optimal disintegration time ( 6,33 ± 0,46 second), low friability (0,99 ±0,00%),), and high hardness (2,092 ±0,27 kg). These findings suggest that Sarang Semut tuber ethanolic extract holds significant potential for further development into standardized traditional medicine.